Fresh and Mechanical Properties of Concrete Containing Oil-Well Cutting Material - Hussein, Nabaz S.; Ibrahim, Rahel Kh. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Oil-well cutting material (OWCM) is a waste generated during the process of oil-well drilling. Its disposal is costly and harmful to the environment. The chemical makeup for the material implies that it might be used as a partial cement replacement in concrete. It is high in calcium oxide, silica, and aluminum oxide, which are the main oxides found in raw materials used to produce cement. Replacing a part of cement by OWCM in concrete mixtures can directly reduce the quantity of the cement used which leads to decreasing the emission of carbon dioxide and solving the disposal problems for the OWCM as well. This process can be considered as a significant step in producing environmentally friendly concrete. This study focuses on investigating the fresh and mechanical properties of different concrete mixes that have different strength grades, containing different percentages of OWCM as a cement replacement. For this purpose, different concrete mixes containing 10%, 15%, 20%, 25%,30%, 35%, and 40% of OWCM as a cement replacement, besides the control Portland cement for the three different concrete strength grades, were prepared. After performing the slump and flow tests, cube specimens were cast and moist-cured for 3, 28, and 90 days and subjected to compression test, whereas 28-day moist-cured cylinder specimens were subjected to splitting tensile test. The test results have revealed that in spite of small reduction in strength with replacing cement by up to 20% of OWCM, the strength of the concrete remains within the designed strength grade ranges.